2021
DOI: 10.1038/s41467-020-20849-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of genome architecture and chromatin function during human B cell differentiation and neoplastic transformation

Abstract: To investigate the three-dimensional (3D) genome architecture across normal B cell differentiation and in neoplastic cells from different subtypes of chronic lymphocytic leukemia and mantle cell lymphoma patients, here we integrate in situ Hi-C and nine additional omics layers. Beyond conventional active (A) and inactive (B) compartments, we uncover a highly-dynamic intermediate compartment enriched in poised and polycomb-repressed chromatin. During B cell development, 28% of the compartments change, mostly in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 118 publications
(200 reference statements)
3
93
2
Order By: Relevance
“…Memory B cells: The dynamic changes in chromatin state and conformation landscape that occurs upon B cell activation and GC transition are largely reversible as cells progress to the memory stage. The epigenetic landscape, transcriptome, chromatin accessibility and 3D organization of quiescent human naive and memory B cell populations are indeed indistinguishable upon unsupervised clustering, nonetheless clearly separated from GC and plasma mature B cells populations (29). Most of I compartments defined in GC B cells, switch back upon memory B cell transition to a compartment organization similar to naive B cells, erasing this layer of 3D organization imprint and allowing memory B-cells priming for GC re-entry.…”
Section: B Cellsmentioning
confidence: 93%
See 4 more Smart Citations
“…Memory B cells: The dynamic changes in chromatin state and conformation landscape that occurs upon B cell activation and GC transition are largely reversible as cells progress to the memory stage. The epigenetic landscape, transcriptome, chromatin accessibility and 3D organization of quiescent human naive and memory B cell populations are indeed indistinguishable upon unsupervised clustering, nonetheless clearly separated from GC and plasma mature B cells populations (29). Most of I compartments defined in GC B cells, switch back upon memory B cell transition to a compartment organization similar to naive B cells, erasing this layer of 3D organization imprint and allowing memory B-cells priming for GC re-entry.…”
Section: B Cellsmentioning
confidence: 93%
“…A recent study demonstrated that in B cells, the naive to GC transition is also characterized by compartmentalization changes and the emergence of a new type of weak, Intermediate (I) compartments, which allow for inter-compartment interactions. I compartments in GC B cells arise from A or B compartments and are enriched for the H3K27me3 mark, containing genes repressed by the PRC (29).…”
Section: B Cellsmentioning
confidence: 99%
See 3 more Smart Citations